Is Psychology a Science? - SILVERMAN, ROBERT E. (Skeptic, 2011)
The article discusses the relationship between psychology and science. The American Psychological Association's spokespersons often use the phrases "the basic science of psychology," or to the "scientific research," when they discuss psychology. In 1879, physiologist Wilhelm Max Wundt argued that in the same way as physics observes the events of the physical world, psychology can observe the events of the mental world.